Correlation of Postoperative Cerebral Oxygen Saturation and Duration of Intensive Care Unit Stay Following Heart Valve Surgery - Putri, Deby Yuliananda Rosa; Irina, Rr. Sinta; Tanjung, Qadri Fauzi (Jurnal Anestesi Perioperatif, 2026)
Background: Postoperative neurological complications and prolonged recovery are key concerns in heart valve surgery, and monitoring regional cerebral oxygen saturation (rScO₂) using Near–Infrared Spectroscopy (NIRS) offers a non–invasive way to assess cerebral oxygenation. This study aimed to evaluate the relationship between perioperative rScO₂ and ICU length of stay and its potential clinical significance.Methods: A cross–sectional, observational, analytic study was conducted in 48 patients undergoing heart valve surgery at Haji Adam Malik General Hospital, Medan. Regional cerebral oxygen saturation was measured at three time points: preoperative (T0), immediately postoperative (T1), and 8 hours post–extubation (T2).Results: Spearman correlation analysis revealed a significant negative relationship between right rScO₂ at T1 and ICU length of stay (r=–0.406; p=0.034), and similarly, left rScO₂ at T1 (r=–0.343; p=0.017), indicating that lower postoperative cerebral oxygenation correlates with longer ICU stays, emphasizing its potential clinical relevance.Discussion: These findings suggest that the immediate postoperative period may represent a critical window in which cerebral oxygenation reflects hemodynamic stability and early recovery trajectory. However, interpretation should be cautious due to the cross–sectional design, small sample size, and lack of adjustment for potential confounders, limiting causal inference.Conclusion: Lower immediate postoperative rScO₂ is associated with prolonged ICU length of stay, suggesting its potential role as an early indicator of recovery trajectory, although causal interpretation remains limited.